2016
DOI: 10.4269/ajtmh.16-0187
|View full text |Cite
|
Sign up to set email alerts
|

Costs Associated with Surgically Treated Cases of Abdominal Cystic Echinococcosis: A Single Center's Experience from 2008 to 2014, Pavia, Italy

Abstract: Abstract. Cystic echinococcosis (CE) is a globally distributed zoonosis caused by the Echinococcus granulosus sensu lato species complex. Four approaches are available for treatment of abdominal CE: surgery, percutaneous aspiration, chemotherapy with albendazole, and watch-and-wait. Allocation of patients to these different treatment options mainly depends on the stage of the cystic lesion. However, as available guidelines are not widely followed, surgery is often applied even without the correct indication ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Differences in healthcare systems and billing systems, distinct methods and parameters used for the cost models of each publication, economic disparities, inflation and diverging price-levels of each country make direct comparisons almost impossible. However, the high costs of surgical interventions were also noted in a previous study from Italy [12]. Based on an Austrian population of 8.7 million inhabitants, and estimated incidence of 0.46 cases /100,000 persons / year, costs for CE accumulated to an estimated 5,660€ per 100,000 inhabitants per year (95%CI 4,006€ - 7,315€).…”
Section: Discussionmentioning
confidence: 58%
“…Differences in healthcare systems and billing systems, distinct methods and parameters used for the cost models of each publication, economic disparities, inflation and diverging price-levels of each country make direct comparisons almost impossible. However, the high costs of surgical interventions were also noted in a previous study from Italy [12]. Based on an Austrian population of 8.7 million inhabitants, and estimated incidence of 0.46 cases /100,000 persons / year, costs for CE accumulated to an estimated 5,660€ per 100,000 inhabitants per year (95%CI 4,006€ - 7,315€).…”
Section: Discussionmentioning
confidence: 58%
“…In fact, as the graph suggests, costs followed a negative trend from 2001 to 2012 and a peak in 2013 ( Fig 6 ). In their paper, Narra et al found out that for 15 surgical patients treated in single center from 2008 to 2014, the surgical intervention related costs ranged from 5,874 to 23,077 per patient, the present study analysed 4239 surgical hospitalization of national database for 14 years, giving for a CE related surgical procedure an average cost of € 8,152; considering the update of remuneration prices across the study period, these findings are not in contradiction [ 41 ].This study show that the geographical breakdown of costs were strictly related to geographical distribution of disease conducted in a previous study with peaks in NUTS 1 Islands and Southern Italy and less financial commitment in the North [ 21 ]. There was an even more marked difference in CE costs related to the population in the various Italian regions ( Fig 3 , Fig 4 ).…”
Section: Discussionmentioning
confidence: 71%
“…In terms of treatment, the stage-matched approach to liver cysts allows a rational choice that avoids ineffective (ABZ or PAIR for CE2 and CE3b cysts) or unnecessary over-treatment. Any surgery on uncomplicated inactive cysts is potentially dangerous and a waste of medical resources [ 1 , 4 , 23 , 28 ].…”
Section: Discussionmentioning
confidence: 99%